Determining the Anthropogenic Greenhouse Gas Contribution to the Observed Intensification of Extreme Precipitation. Issue 12 (22nd June 2020) - Paik, Seungmok; Min, Seung‐Ki; Zhang, Xuebin; Donat, Markus G.; King, Andrew D.; Sun, Qiaohong
Abstract: This study conducts a detection and attribution analysis of the observed changes in extreme precipitation during 1951–2015. Observed and CMIP6 multimodel simulated changes in annual maximum daily and consecutive 5‐day precipitation are compared using an optimal fingerprinting technique for different spatial scales from global land, Northern Hemisphere extratropics, tropics, three continental regions (North America and western and eastern Eurasia), and global "dry" and "wet" land areas (as defined by their average extreme precipitation intensities). Results indicate that anthropogenic greenhouse gas influence is robustly detected in the observed intensification of extreme precipitation over the global land and most of the subregions considered, all with clear separation from natural and anthropogenic aerosol forcings. Also, the human‐induced greenhouse gas increases are found to be a dominant contributor to the observed increase in extreme precipitation intensity, which largely follows the increased moisture availability under global warming. Plain Language Summary: Human influences have been identified in the observed intensification of extreme precipitation at global and continental scales, but quantifying the contribution of greenhouse gas increases remains challenging. Here, we isolate anthropogenic greenhouse gas impacts on the observed intensification of extreme precipitation during 1951–2015 by comparing observations with CMIP6 individual forcing experiments. Results show that greenhouse gas influences are detected over the global land, Northern Hemisphere extratropics, western and eastern Eurasia, and global "dry" and "wet" regions, which are separable from other external forcings such as solar and volcanic activities and anthropogenic aerosols. The human‐induced greenhouse gas increases are also found to explain most of the observed changes in extreme precipitation intensity, which are consistent with the increased moisture availability with warming. Our results provide the first quantitative evidence for the dominant influence of human‐made greenhouse gases on extreme precipitation increase. Key Points: Causes of the observed intensification of extreme precipitation during 1951 to 2015 are examined using CMIP6 multimodel simulations Results from optimal fingerprinting analyses show that the anthropogenic signals are robustly detected at hemispheric and continental scales The observed increase in extreme precipitation is mostly attributed to anthropogenic greenhouse gas increases